GREEN SYNTHESIS OF SULFUR NANOPARTICLES USING ZIZIPHUS-SPINA TREE LEAVES AND THEIR ANTIBACTERIAL ACTIVITY - R. M. Hasan; M. M. Sirhan; H. Kh. Ali (مجلة الأنبار للعلوم الزراعية)
The main goal of this research was to use an environmentally friendly, simple, and sustainable method to produce sulfur nanoparticles using the aqueous extract of Ziziphus-spina tree leaves and hydrochloric acid. The prepared sulfur nanoparticles were characterized using various techniques, including X-ray diffraction (XRD), infrared spectroscopy (FT-IR), scanning electron microscope (SEM), transmission electron microscope (TEM), and atomic force microscopy (AFM). XRD results showed that their average diameter was 9.26 nm and the sulfur nanoparticles were well-crystalline and highly pure. SEM images revealed the formation of spherical particles. FT-IR analysis showed a sharp peak for sulfur nanoparticles at 460 cm-1, indicating that their surface contained a new chemical bond.  This shows that the carbonyl residue of amino acids found in the material extracted from the Ziziphus spina tree may be a means for linking it to sulfur molecules.  This extract acts as a stabilizer for the synthesized sulfur nanoparticles. The antibacterial activity of the prepared SNPs was tested against 2 species each of gram-positive (Staphylococcus aureus and Staphylococcus epidermidis) and gram-negative (Escherichia coli and Klebsiella pneumonia) bacteria using the agar well diffusion method. The results show that the SNPs have antibacterial activity